Fading authority, rising depression: occupational identity and mental health among China’s retired danwei leaders - Zhang, Xubin; Yang, Yang; He, Li; Wang, Zihan (Frontiers in Psychiatry, 2025)
Late-life depression is a significant public health concern, yet its relationship with occupational identity in retirement remains underexplored. This study investigates whether retired Danwei leaders—individuals who formerly held leadership roles within China’s state-affiliated work units—experience higher levels of depressive symptoms compared to other retirees. Using nationally representative data from the 2016 and 2018 waves of the China Longitudinal Aging Social Survey (CLASS), we apply mixed-effects regression models to examine the association between occupational identity and depression, along with the underlying mechanisms. The results indicate that retired Danwei leaders exhibit significantly higher levels of depression, and this association appears to be linked to declining physical health and diminished interpersonal relationships following retirement. These findings offer new empirical evidence on the mental health implications of high-status occupational identity in post-retirement life and underscore the need for targeted mental health interventions and social support strategies for this vulnerable subgroup of older adults in China.